Soveršenstvovanie i ocenka special'noj fiziceskoj podgotovlennosti junych tchekvondistov sredstvami elektronnogo trenirovocnogo oborudovanija - Mut'ev, A. V.; Mišin, N. P. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
Modern equipment based on computer technology improves the efficiency of the training process, the timeliness and accuracy of the control procedure of the special physical preparedness of Taekwondo athletes. This research is devoted to the study of the possibilities of using the e-sparring system "Zemita" for training process and monitoring the special physical preparedness of young Taekwondo athletes. Confirmed the possibility of using e-sparring system for the improvement and evaluation of the special physical preparedness of athletes, competitions and recreational activity. The levels of special endurance of young Taekwondo athletes 6-7 years old are determined.